The Cordillerans in the academe a content analysis of the portrayal of the indigenous Cordillera people in academic textbooks and references - de La Cruz, Charlito 1977-
The mass media hand in hand with the Western-oriented educational system has discriminated continuously the national minorities in the Philippines, portraying them profusely as primitive, barbaric, and savage. This is true with the Cordillerans, particularly in books that are used in the academe where they are portrayed subjectively, negatively, and inaccurately. The traits and practices, and their identity as Cordilleran, are branded as primitice, backward, and obsolete, thus inferior. Worse, this is even institutionalized in the Philippine government system. This study reveals that there was a conscious effort by the "majority" to discriminate the Cordillerans. It was meant to acculturate them to the Western culture and way of life, for political and economic reasons. However, there have been efforts ever since, to end this unwanted situation, efforts that transformed into collective actions. And this thesis is just but a contribution to the historical but fast growing movement for self-determination and genuine autonomy of the Cordillerans and other national minorities. It is an effort directed to better awareness of the issue of the minorities, and discrimination per se, particular in the academe where enlightened minds supposedly reside.